Ensino de imitação generalizada para crianças com transtorno do espectro autista - Brandão, Vanessa Paula de Souza (2024)
Autism Spectrum Disorder (ASD) is a neurodevelopmental disorder characterized by impairments in communication and social interaction skills, restricted and repetitive patterns of behaviors, interests or activities. A deficit repertoire, which is considered a behavioral wedge and, therefore, of extreme importance for creating the repertoire of the person with ASD is that of generalized imitation, as it provides the learning of a range of new behaviors, without the need for direct teaching. and for reducing behavioral barriers. The present research aims to evaluate whether teaching multiple imitation exemplars will be sufficient to guarantee widespread imitation for children with ASD and validate Goyos' (2018) protocols. The Generalized Imitation acquisition criterion was defined as achieving 100% correct performance in three successive applications of a protocol developed specifically for this purpose. In a multiple-baseline design across four participants, an initial baseline measure of generalized imitation behavior was administered, followed by individual teaching of multiple imitation exemplars, and again by applications of the generalized imitation measure. The results showed that two of the four participants reached criterion in generalized imitation performance after four and eight directly taught exemplars. Possible variables that affect generalized imitation performance are discussed as well as implications for teaching generalized imitation.